2015
DOI: 10.1016/j.matlet.2015.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of Nb3Sn coatings on Cu substrates

Abstract: a b s t r a c tThis work aims at contributing to the development of superconducting Nb 3 Sn thin films for possible applications, as for instance in superconducting radio frequency (SRF) cavities. The synthesis of Nb-Sn coatings was carried out on copper substrates by electrodeposition from 1-butyl-3-methylimidazolium chloride (BMIC) ionic liquids containing SnCl 2 and NbCl 5 . Cyclic voltammetric curves were recorded to identify the reduction potentials of Nb and Sn ionic species. Electrodeposition was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…For most annealing approaches, phase pure Nb 3 Sn is only formed above 930 C. 14 For electrochemical approaches in combination with annealing, the lowest formation temperature of superconducting Nb 3 Sn was reported to be 630 C, requiring additional Cu as a flux medium. 17 However, Cu interdiffusion at this temperature results in a severe decrease of performance, and only a considerable further reduction of growth temperature (as reported here) would allow the combination of Nb 3 Sn with Cu. Previously reported approaches potentially lead to inhomogeneous or graded distributions of Nb and Sn and, furthermore, to the formation of non-superconducting phases limiting the desired performance since they all require annealing.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…For most annealing approaches, phase pure Nb 3 Sn is only formed above 930 C. 14 For electrochemical approaches in combination with annealing, the lowest formation temperature of superconducting Nb 3 Sn was reported to be 630 C, requiring additional Cu as a flux medium. 17 However, Cu interdiffusion at this temperature results in a severe decrease of performance, and only a considerable further reduction of growth temperature (as reported here) would allow the combination of Nb 3 Sn with Cu. Previously reported approaches potentially lead to inhomogeneous or graded distributions of Nb and Sn and, furthermore, to the formation of non-superconducting phases limiting the desired performance since they all require annealing.…”
Section: Introductionmentioning
confidence: 53%
“…Previously reported approaches potentially lead to inhomogeneous or graded distributions of Nb and Sn and, furthermore, to the formation of non-superconducting phases limiting the desired performance since they all require annealing. 4,17,18 Tin evaporation is the first and most advanced process for actual production of cavities. Sputtering approaches are significant as an alternative route of coating copper cavities.…”
Section: Introductionmentioning
confidence: 99%
“…This would be the first time that Nb 3 Sn is reproducibly formed directly in molecular form and at much lower temperatures (100 °C-130 °C) than in any other state-of-theart method, which is by solid diffusion at very high temperature (650 °C+). The results of this latter work were published in a separate journal [10].…”
Section: Introductionmentioning
confidence: 95%
“…In these studies, many beneficial results have been obtained with regard to the electrochemical behaviour of different copper alloys. In addition, investigations showed that the BMIC ionic liquid was very suitable for the electrodeposition of metals and alloys [8,9].…”
Section: Introductionmentioning
confidence: 99%